Pick-Up Savings System to Improve the Financial Management Capabilities of Village Communities: Analysis of The Role of Village-Owned Enterprises - SISKAWATI, Eka; YULIA, Meri; ZAHARA, Zahara (PT Keberlanjutan Strategis Indonesia, 2021)
The business entity owned by the Village, as an economic institution at the village level, established to improve the economic welfare of the village community. One of the efforts made is to increase awareness behavior in saving. The behavior of villagers in saving is often still short-term oriented, so most villagers have not been able to manage finances to anticipate their financial problems in the future. Therefore, research on the role of BUMDes as a village-scale economic institution in improving the financial management capabilities of the village community is very important to do. The purpose of this research is to find out how the role of business entities have in improving the financial management capabilities of the community through savings products with a savings pick-up system. This research uses a qualitative approach with case study methods in Village Owned Enterprises (BUMDes) Pakandangan Emas. Data collection techniques are conducted through interviews and observations in the field. This research found that Unit sharia savings business in BUMDes Pakandangan Emas can shape people's behavior in long-term financial management. This behavior is formed mainly through a savings system that is directly picked up to the community.